Metabolic management of microenvironment acidity in glioblastoma - Seyfried, Thomas N.; Arismendi-Morillo, Gabriel; Zuccoli, Giulio; Lee, Derek C.; Duraj, Tomas; Elsakka, Ahmed M.; Maroon, Joseph C.; Mukherjee, Purna; Ta, Linh; Shelton, Laura; D'Agostino, Dominic; Kiebish, Michael; et al. (Frontiers in Oncology, 2022)
Glioblastoma (GBM), like most cancers, is dependent on fermentation metabolism for the synthesis of biomass and energy (ATP) regardless of the cellular or genetic heterogeneity. The transition from respiration to fermentation arises from the well-documented defects in the number, the structure, and the function of mitochondria and mitochondrial-associated membranes in GBM tissue. Glucose and glutamine are the major fermentable fuels that drive GBM growth. The waste products of GBM cell fermentation (lactic acid, glutamic acid, and succinic acid) will acidify the microenvironment and are largely responsible for drug resistance, enhanced invasion, immunosuppression, and metastasis. Besides surgical debulking, therapies used for GBM management (radiation, chemotherapy, and steroids) enhance microenvironment acidification and, although often providing a time-limited disease control, will thus favor tumor recurrence and complications. The simultaneous restriction of glucose and glutamine, while elevating non-fermentable, anti-inflammatory ketone bodies, can help restore the pH balance of the microenvironment while, at the same time, providing a non-toxic therapeutic strategy for killing most of the neoplastic cells.